Pemodelan Arsitektur Sistem Informasi Pemagangan dan Penempatan Kerja Menggunakan Framework TOGAF (Studi kasus: Politeknik LP3I) - Ahmad Sahi (LPPM POLITEKNIK LP3I BANDUNG, 2023)
LP3I Polytechnic is a higher education institution that specializes in workplace education. A strong approach is needed for this higher education institution to fulfill its educational duties. To support this business strategy, top-notch information systems and information technology are required. The TOGAF-ADM (Open Group Architecture Framework-Architecture Development Method) is used in this architecture modeling of the internship and employment information system. A better grasp of how to develop enterprise architecture models will be given through a number of TOGAF ADM activities for enterprise architecture development. Based on the requirements of numerous organizations, including both industrial companies and colleges, TOGAF-ADM is a generic and simple implementation technique. In this journal, 8 steps will be discussed using the TOGAF framework in implementing it in the internship and employment section at the LP3I Polytechnic including Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities and Solutions, Migration Planning, Implementation Governance, Change Management.